Minimasi Biaya Persediaan Ikan Kakap Merah PT. MMU Metode Economic Order Quantity (EOQ) - Arifin, Defitria Sabrina Firdaus; Nugraha, Isna (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. MMU is an industry engaged in processing marine fish. The aim of this research is to minimize the cost of snapper supplies so that the production process becomes more efficient. The analysis begins with data on demand for red snapper in 2023. The movement of recorded demand shows fairly stable fluctuations, although there are some significant declines in certain months, data on ordering costs and storage costs, including raw material prices, ordering frequency, costs forklift, and ice cube costs, have been obtained to account for the total cost of raw material inventory. Data on fish demand, ordering costs, storage costs, and inventory factors were analyzed, resulting in an optimal order quantity of 298.98 kg per order with an order frequency of 6 times a year. Cost analysis shows potential savings of Rp. 3,078,677.43, safety stock of 127 kg and re order point of 42 kg. This research provides insight into the efficiency of inventory management at PT. MMU and its important implications for stock control in the fishing industry